Global Financial Stability Report, April 2008 : Containing Systemic Risks and Restoring Financial Soundness. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2008)
The events of the past six months have demonstrated the fragility of the global financial system and raised fundamental questions about the effectiveness of the response by private and public sector institutions. The report assesses the vulnerabilities that the system is facing and offers tentative conclusions and policy lessons. The report reflects information available up to March 21, 2008.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet